General Description of Methods for Protecting Inheritance Rights - Nishonova Nigora Tolibovna (Scientific Trends, 2026)
The article provides a general overview of the methods for protecting inheritance rights as an essential component of the legal regulation of succession relations. It examines substantive and procedural legal remedies aimed at safeguarding the rights and legitimate interests of heirs, as well as the grounds for their application. Particular attention is paid to typical violations of inheritance rights, types of legal claims used in judicial practice, and challenges of law enforcement. The author emphasizes the importance of an effective system of inheritance rights protection for ensuring legal certainty and justice.
Keywords: Inheritance law, protection of inheritance rights, heir, decedent, remedies, judicial protection, property rights, civil law.